Optimization of Booster Pump Performance Through Reliability Centered Maintenance (RCM) and Failure Mode and Effect Analysis (FMEA) at Wisma PMI - Surasa, Surasa; Rahardian, Slamet (Asosiasi Dosen Muda Indonesia, 2026)
Maintenance of the booster pump machine at the PMI guesthouse building located on Jl. Wijaya No. 63 South Jakarta is an obligation for operational management. The booster pump machine is the core of driving the distribution of water needs throughout the building, data obtained from engineering in 2023 experienced damage 70 times, the damage had an impact on tenant complaints because the engine was loud and frequent. To overcome water supply problems and also the noise so as not to cause complaints for consumers which had a long- term impact on reducing rental space occupancy in the property business, engineering and evaluation of the maintenant system was immediately carried out using the reliability centered maintenant (RCM) method and failure mode and effect analysis. (FIMEA) is one of the steps taken in an effort to resolve complaints regarding the operational failure of the booster pump. After analyzing the data using the RCM strategy and also FIMEA to determine the potential and damage level scores, if the results of the analysis are applied it is estimated that an optimization of the booster pump system can be obtained with the damage level decreasing by up to 20% and also reducing the engine noise level by up to 20 db.